Never After : The Broken Mirror - Book 3 - De la Cruz, Melissa, 1971- (New York, NY : Roaring Brook Press, 2022)
In their third adventure, Filomena and company set off to Snow Country, rescue Lord Sharif of Nottingham, reverse a spell that turned Prince Charming into a Frog, and form the League of the Seven-fearless warriors devoted to fighting the orges at any cost.
Keywords: Good and evil -- Juvenile fiction; Magic -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Adventure stories; Friendship -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Fantasy -- Juvenile fiction; Good and evil -- Fiction; Magic -- Fiction; Characters in literature -- Fiction; Adventure and adventurers -- Fiction; Friendship -- Fiction; Racially mixed people -- Fiction; Fantasy; Juvenile fiction